Art, Environment, and Sustainability: Case Studies on the Philippine Art Practice. (1st December 2016) - Abeledo, Ryanorlie B.; Vince Cruz, Chona Camille E.
Abstract : Art is a powerful tool for conveying ideas. It transcends various modes of communication, allowing it to trigger mental, emotional, and physical responses from its target audience. Its effectiveness as a tool for environmental advocacy, however, is limited by the sustainability of the practice and the materials used. Contemporary art practices in the Philippines have found ways to support the campaign for environmental sustainability by using repurposed materials that result in a decreased carbon footprint in the art production process, while conveying environmental themes. This evaluative article presents two case studies tackling the new-found indigenous art practice of the Talaandig tribe in the province of Bukidnon, Philippines, and the contemporary art practice of select assemblage artists from Metro Manila using found objects. This article illustrates how Filipino artists in both the indigenous and contemporary art scenes are supporting the global campaign of environmental conservation in message and action.